Slum improvement in India: determinants and approaches. Issue 7 (3rd October 2017) - De, Indranil
Abstract: This paper investigates living conditions in Indian slums, extent of improvement of basic services between 2002 and 2012 and determinants of improvement based on National Sample Survey data. The pace of slum improvement has increased over the study period. Slums devoid of basic services have reduced in 2012 as compared to 2002. Security of tenure, strengthened especially through notification of slums, appears to be one of the most important determinants of slum upgradation. Improvements of electricity and water supply spur improvements of other basic services. Better approach roads lead to better housing but motorable pucca (tarmac) approach road or proximity to motorable road reduces likelihood of better housing. Government is the major provider of services in slums. The role of NGOs in improvement of basic services within slums has declined over time along with decline in associations for slum improvement. The paper advocates transfer of full property rights to slum dwellers and integration of different institutions for slum improvement.